The tin church - Haden, Rosamund (Department of English Language and Literature, 2014)
Human bones are discovered on the farm Hebron near Swaziland where two old women, Catherine and Maria, live. Their memories are stirred and disturbed by the discovery. Two young girls weave a close bond of friendship on the farm. Their childhood promises made in the tin church on the hill above Hebron are to have lasting repercussions on the shape of their lives. The church becomes their haven where they know they can always find each other. When Catherine's parents split up, and Catherine is taken to England, Maria still goes to the church, for there she is close to Catherine, and can see visions of her far away.